Lewis acid capping of a uranium(v) nitride via a uranium(iii) azide molecular square. Issue 33 (24th March 2020) - Boreen, Michael A.; Rao, Guodong; Villarreal, David G.; Watt, Fabian A.; Britt, R. David; Hohloch, Stephan; Arnold, John
Abstract : Addition of B(C6 F5 )3 to a tetrameric uranium(iii ) azide-bridged molecular square induced N2 loss and formation of a uranium(v ) borane-capped nitride. Abstract : Reaction of (Cp iPr4 )2 UI with NaN3 resulted in formation of tetrameric uranium(iii ) azide-bridged 'molecular square' [(Cp iPr4 )2 U(μ-η 1 :η 1 -N3 )]4 (1 ). Addition of B(C6 F5 )3 to 1 induced loss of N2 at room temperature, yielding the uranium(v ) borane-capped nitrido (Cp iPr4 )2 U(μ-N)B(C6 F5 )3 (2 ).